Faktor-Faktor Risiko Preeklamsi pada Ibu Hamil Berdasarkan Karakteristik Maternal di Kabupaten Banyumas - Wilis Dwi Pangesti; Junia Rahmani Fauzia1 (2022)
Preeclampsia is the main cause of maternal death in Indonesia with an incidence of 3-10%. An increase in the incidence of pregnancy with preeclampsia occurred in Banyumas Regency in the period 2019 and 2020 with a mortality rate of preeclampsia with accompanying complications of 27.3%. The discovery of risk factors for preeclampsia at gestational age <20 weeks is currently one of the programs to reduce the incidence of preeclampsia in Banyumas Regency. This study aims to determine the risk factors for preeclampsia in pregnant women based on maternal characteristics. This research is a descriptive study with a subject of 323 pregnant women in the area of Puskesmas, Banyumas Regency. The sampling technique used purpose sampling. Data was taken from 5 health centers. Data analysis used univariate analysis to determine the number and percentage. The results showed that the order of the highest percentages was multiparity at 74.3%, followed by the age of pregnant women >35 years of as much as 14.2%, BMI 30 kg/m2 as much as 9.9%, and a history of hypertension as much as 1.9%.